Comparison of the prevalence of hyperuricemia in families of patients with and without gouty arthritis among Balinese people - Gede Kambayana; T R Putra (Indonesian Rheumatology Association, 2011)
Background: Gout is a metabolic disorder caused by hyperuricemia, which results from changes in uric acid metabolism. Both internal (e.g., genetics) and external factors (e.g., diet, habits, comorbidities) play role in the occurrence of hyperuricemia and the difference of hyperuricemia prevalence in different populations.Objective: To compare the prevalence of hyperuricemia in families of gout and non-gout patients among Balinese people.Methods: This cross-sectional study was carried out at the rheumatology clinic at Sanglah Hospital, Denpasar. Samples were collected using consecutive method and consisted of gout and non-gout patients. Several characteristics (alcohol and purine consumption,medications, blood pressure, body mass index, serum uric acid level, and serum creatinine) in both groups were collected and compared. Family members (fi rstdegree relatives) of patients in each group were also recruited and had their serum uric acid level measured and compared.Results: A total of 46 patients and 116 family members (23 patients and 58 family members in each group) were enrolled. Among gout patients, there was signifi cantlyhigher prevalence of hyperuricemia, serum uric acid level, blood pressure, and serum creatinine; and lower creatinine clearance compared with the non-gout patients. There was signifi cantly higher prevalence of hyperuricemia among families of gout patients comparedwith families of non-gout patients (60.3 vs. 29.3%, respectively; p = 0.001), with a prevalence ratio of 2.06. Mean serum uric acid level of the family members of gout patients were also signifi cantly higher than the family members of non-gout patients (7.24 (SD 1.74) vs. 5.92 (SD 1.63) mg/dL, respectively; p = 0.000).Conclusion: Among Balinese people in this study, significantly higher prevalence of hyperuricemia and mean serum uric acid level was observed in families of gout patients compared with families of non-gout patients.